Crossmodal Congruency Enhances Performance of Healthy Older Adults in Visual-Tactile Pattern Matching - Higgen, Focko L.; Heine, Charlotte; Krawinkel, Lutz; Göschl, Florian; Engel, Andreas K.; Hummel, Friedhelm C.; Xue, Gui; Gerloff, Christian (Frontiers in Aging Neuroscience, 2020)
One of the pivotal challenges of aging is to maintain independence in the activities of daily life. In order to adapt to changes in the environment, it is crucial to continuously process and accurately combine simultaneous input from different sensory systems, i.e., crossmodal integration. With aging, performance decreases in multiple cognitive domains. The processing of sensory stimuli constitutes one of the key features of this deterioration. Age-related sensory impairments affect all modalities, substantiated by decreased acuity in visual, auditory or tactile detection tasks. However, whether this decline of sensory processing leads to impairments in crossmodal integration remains an unresolved question. While some researchers propose that crossmodal integration degrades with age, others suggest that it is conserved or even gains compensatory importance. To address this question, we compared behavioural performance of older and young participants in a well-established crossmodal matching task, requiring the evaluation of congruency in simultaneously presented visual and tactile patterns. Older participants performed significantly worse than young controls in the crossmodal task when being stimulated at their individual unimodal visual and tactile perception thresholds. Performance increased with adjustment of stimulus intensities. This improvement was driven by better detection of congruent stimulus pairs (p<0.01), while detection of incongruent pairs was not significantly enhanced (p=0.12). These results indicate that age-related impairments lead to poor performance in complex crossmodal scenarios and demanding cognitive tasks. Performance is enhanced when inputs to the visual and tactile systems are congruent. Congruency effects might therefore be used to develop strategies for cognitive training and neurological rehabilitation.